2018
DOI: 10.3390/su10113875
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Concrete with Waste Recycled Plastic: A Review

Abstract: The abundance of waste plastic is a major issue for the sustainability of the environment as plastic pollutes rivers, land, and oceans. However, the versatile behavior of plastic (it is lightweight, flexible, strong, moisture-resistant, and cheap) can make it a replacement for or alternative to many existing composite materials like concrete. Over the past few decades, many researchers have used waste plastic as a replacement for aggregates in concrete. This paper presents a comprehensive review of the enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 77 publications
(171 reference statements)
5
126
1
14
Order By: Relevance
“…erefore, as the amount of plastic aggregates increased, the slump increased due to a larger area of smooth surface. It was also found that the density of concrete decreased proportionally with increasing replacement of plastic aggregates, as plastics have lower density than natural aggregates [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…erefore, as the amount of plastic aggregates increased, the slump increased due to a larger area of smooth surface. It was also found that the density of concrete decreased proportionally with increasing replacement of plastic aggregates, as plastics have lower density than natural aggregates [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…Slump is the most commonly used variable for determining the workability performance of concrete in its fresh state. e particle size distribution, particle shape, water-binder (w/b) ratio, temperature, and the amount of admixture added to the concrete mix directly influence the workability properties of concrete [39].…”
Section: Packed Platy Particles Of Mkmentioning
confidence: 99%
“…Among suspected drawbacks of the use of plastic aggregate, is the lower mechanical properties such as lower flexural strength [19], lower dynamic elastic modulus [20]. There are also limits of the percentage of using recycled plastic, such as 50% [21].…”
Section: Introductionmentioning
confidence: 99%